1990
DOI: 10.2307/2426557
|View full text |Cite
|
Sign up to set email alerts
|

Microgeographic Adaptation to Temperature in Pitch Pine Progenies

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.ABSTRACT.-Localized variation in cold tolerance of pitch pine (Pinus rigida Mill.) seedlings from an area including a large frost pocket was examined over an autumn, winter and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Elucidating such processes thus requires further empirical research on species displaying evident diversification at fine spatial scales. Given that some of the best examples of microgeographic adaptation involve mainly sedentary organisms such as plants (Steiner & Berrang, 1990; Antonovics, 2006; Hendrick et al, 2016), we aimed to investigate such processes in a more mobile organism, wherein the signal of microgeographic adaptation may be less evident and underappreciated as a factor affecting the rate of diversification under gene flow.…”
Section: Introductionmentioning
confidence: 99%
“…Elucidating such processes thus requires further empirical research on species displaying evident diversification at fine spatial scales. Given that some of the best examples of microgeographic adaptation involve mainly sedentary organisms such as plants (Steiner & Berrang, 1990; Antonovics, 2006; Hendrick et al, 2016), we aimed to investigate such processes in a more mobile organism, wherein the signal of microgeographic adaptation may be less evident and underappreciated as a factor affecting the rate of diversification under gene flow.…”
Section: Introductionmentioning
confidence: 99%
“…Good and Good (1975) in a greenhouse/nursery experiment with New Jersey P. rigida found that seedlings originating from dwarf populations were shorter, had less biomass, and reproduced earlier than seedlings originating from normal-stature populations. Using a commongarden approach, Steiner and Berrang (1990) found greater cold tolerance in P. rigida seedlings originating from a localized ''cold pocket'' depression in Pennsylvania than in seedlings originating from nearby, warmer habitats.…”
Section: Discussionmentioning
confidence: 96%
“…This assumption is supported by various empirical fi ndings (Nosil & Crespi, 2004). However, Richardson & Urban (2013) suggest that some studies seriously challenge the presumption that local adaptation occurs only at large geographical scales (Steiner & Berrang, 1990;Kavanagh et al, 2010;Willi & Hoffmann, 2012;Richardson et al, 2014). There is, therefore, accumulating evidence that we should revise theoretical presumptions of local adaptation in terms of spatial scale.…”
Section: Population Samples and Microhabitat Characteristics At The Lmentioning
confidence: 99%